Characterization and modeling of multiple friction pendulum isolation system with numerous sliding interfaces. - Tsai, C.S (Earthquake engineering & structural dynamics.)
In order to systematically investigate the mechanical characteristic of a multiple friction pendulum system with numerous concave sliding interfaces and one articulated slider located between these concave sliding interfaces, general mathematical formulations have been derived from the proposed concept of subsystems. In addition, based on the plasticity theory, an analytical model called the multiple yield and bounding surfaces model has been proposed in this study. On the basis of the subsystem concept, the mathematical formulations and the plasticity model for the entire system can be obtained via the general formulations for each subsystem. The first subsystem includes the concave sliding interfaces above the articulated slider and the second subsystem consists of the concave sliding interfaces below the articulated slider. The proposed plasticity model has two separate groups of multiple yield and bounding surfaces. The first and second groups are adopted to model the mechanical behavior of the sliding motions of the first and second subsystems, respectively. The connection of these two subsystems in series forms the mechanical characteristic of the entire MFPS isolation system. By virtue of the derived mathematical formulations and the proposed plasticity model, the phenomena of the sliding motions of the MFPS isolator with numerous concave sliding interfaces under uni- and bi-directional cyclical loadings can be clearly understood. Numerical analyses are in good agreement with the experimental results and infer that the natural frequency and damping effect of the MFPS isolator with multiple concave sliding interfaces change continually during earthquakes and are controllable through appropriate designs.